In Astrocytes the Accumulation of the Immunity-Related GTPases Irga6 and Irgb6 at the Vacuole of Toxoplasma gondii Is Dependent on the Parasite Virulence - Felix P. Lubitz; Daniel Degrandi; Klaus Pfeffer; Anne K. Mausberg (The Scientific World Journal)
Toxoplasma gondii is an obligate intracellular protozoan parasite responsible for a common infection of the central nervous system. Interferon (IFN)γ is the key cytokine of host defence against T. gondii. However, T. gondii strains differ in virulence and T. gondii factors determining virulence are still poorly understood. In astrocytes IFNγ primarily induces immunity-related GTPases (IRGs), providing a cell-autonomous resistance system. Here, we demonstrate that astrocytes prestimulated with IFNγ inhibit the proliferation of various avirulent, but not virulent, T. gondii strains. The two analyzed immunity-related GTPases Irga6 and Irgb6 accumulate at the PV only of avirulent T. gondii strains, whereas in virulent strains this accumulation is only detectable at very low levels. Both IRG proteins could temporarily be found at the same PV, but did only partially colocalize. Coinfection of avirulent and virulent parasites confirmed that the accumulation of the two analyzed IRGs was a characteristic of the individual PV and not determined by the presence of other strains of T. gondii in the same host cell. Thus, in astrocytes the accumulation of Irga6 and Irgb6 significantly differs between avirulent and virulent T. gondii strains correlating with the toxoplasmacidal properties suggesting a role for this process in parasite virulence.